Cisplatin-induced vestibular hair cell lesion-less damage at high doses - Ding, Dalian (J Otol, 2018)
Cisplatin, a widely used anticancer drug, damages hair cells in cochlear organotypic cultures at low doses, but paradoxically causes little damage at high doses resulting in a U-shaped dose-response function. To determine if the cisplatin dose-response function for vestibular hair cells follows a similar pattern, we treated vestibular organotypic cultures with doses of cisplatin ranging from 10 to 1000 μM. Vestibular hair cell lesions progressively increased as the dose of cisplatin increased with maximum damage occurring around 50–100 μM, but the lesions progressively decreased at higher doses resulting in little hair cell loss at 1000 μM. The U-shaped dose-response function for cisplatin-treated vestibular hair cells in culture appears to be regulated by copper transporters, Ctr1, ATP7A and ATP7B, that dose-dependently regulate the uptake, sequestration and extrusion of cisplatin.